Understanding trance states from the perspective of South African traditional healers - in relation to psychosis - Masia, Ntombifuthi Thato (Rhodes University, Faculty of Humanities, Department of Psychology)
Studies conducted on psychosis, sleep and trance states have indicated that the phenomenon of trance occurs quite similarly to that of psychosis. Trance states (or, altered states of consciousness) are defined as mental states in which there is an alteration in the informational or representational relationships between consciousness and the world, whereby the mechanisms of consciousness have an increased tendency to produce misrepresentations like hallucinations, delusions and memory or temporal distortions. This research study aimed to contribute to the knowledge of trance states, particularly as represented by the language and social processes of traditional healers in South Africa, and as experienced by them. This knowledge is geared towards providing insight on the experience and treatment of the similarly occurring phenomenon of psychosis in clinical settings. Through a qualitative study, this research found that strategies of exploration, building recognition and familiarity, and self-monitoring are used by traditional healers to reduce the distress caused by intrusive and disruptive symptoms of trance, as well as to maintain a stable self-identity while experiencing trance states.
Keywords: Trance; Psychoses; Altered states of consciousness; Healers -- South Africa; Healers -- South Africa -- Attitudes; Mental health services -- South Africa; Psychoses -- Alternative treatment; Psychoses -- Alternative treatment -- Moral and ethical aspects